If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(5x + 4) = 4x + -33 Reorder the terms: 8x + -1(4 + 5x) = 4x + -33 8x + (4 * -1 + 5x * -1) = 4x + -33 8x + (-4 + -5x) = 4x + -33 Reorder the terms: -4 + 8x + -5x = 4x + -33 Combine like terms: 8x + -5x = 3x -4 + 3x = 4x + -33 Reorder the terms: -4 + 3x = -33 + 4x Solving -4 + 3x = -33 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 3x + -4x = -33 + 4x + -4x Combine like terms: 3x + -4x = -1x -4 + -1x = -33 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -1x = -33 + 0 -4 + -1x = -33 Add '4' to each side of the equation. -4 + 4 + -1x = -33 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -33 + 4 -1x = -33 + 4 Combine like terms: -33 + 4 = -29 -1x = -29 Divide each side by '-1'. x = 29 Simplifying x = 29
| t-7-29=419 | | 8+3(4y+5)= | | 20x+15y=250 | | 9x+5=3x+1 | | -6x+9-3(x-1)=-(5x-7)-3x+3 | | 20y+15y=250 | | 2x-1x-1x-3x= | | 16b^3+52b^2-48b= | | 8x+8-6x=3+x+1 | | cp^2+-1dp=k | | -0-24=8+0 | | -[10x-(20x+7)]=7+(9x+10) | | 27x-1=15x-72x+7 | | 6x-3(10-x)= | | 27x-1=15x | | 9x-3(3-2x)=5(x-4)-29 | | 638=n-134 | | x(x+1)-380=0 | | 638=n+34 | | w^2+25w-750=0 | | 21x^2-11x+40=0 | | 6(-2+7k)=-12-4k | | 3(3y-1)(2y)=4 | | 3x-(4x-4)= | | 4x+3(x-6)=4(x-3) | | 15s^2-34s+15= | | 1/4w-5=-3 | | 123+k=649 | | 14x+19x-8+1=-2x+1-8 | | 3-2i=-5 | | -y^2=6y+9 | | 5x-3x+12=x+8 |